Geometric Phase and Localized Heat Diffusion. Issue 32 (10th July 2022) - Qi, Minghong; Wang, Dong; Cao, Pei‐Chao; Zhu, Xue‐Feng; Qiu, Cheng‐Wei; Chen, Hongsheng; Li, Ying
Abstract: Many unusual wave phenomena in artificial structures are governed by their topological properties. However, the topology of diffusion remains almost unexplored. One reason is that diffusion is fundamentally different from wave propagation because of its purely dissipative nature. The other is that the diffusion field is mostly composed of modes that extend over wide ranges, making it difficult to be rendered within the tight‐binding theory as commonly employed in wave physics. Here, the above challenges are overcome and systematic studies are performed on the topology of heat diffusion. Based on a continuum model, the band structure and geometric phase are analytically obtained without using the tight‐binding approximation. A deterministic parameter is found to link the geometric phase with the edge state, thereby proving the bulk‐boundary correspondence for heat diffusion. The topological edge state is experimentally demonstrated as localized heat diffusion and its dependence on the boundary conditions is verified. This approach is general, rigorous, and able to reveal rich knowledge about the system with great accuracy. The findings set up a solid foundation to explore the topology in novel thermal management applications. Abstract : Topological thermal metamaterials are presented. An accurate theoretical framework is established to study the geometric phase and dynamics of the thermal lattices. The topological properties of diffusive systems and localized heat diffusion protected by the topological edge states are revealed. The work can be applied to facilitate the heat dissipation of hot spots.